Feminist Collections, v.8. no.3 (spring 1987) - (:unkn) unknown (My University, 1987)
Subtitle: A Quarterly of Women's Studies Resources. 36p.
FROM THE EDITORS: Some parting thoughts from Cathy Loeb. FEMINIST VISIONS: "Talking Story": An Innovative Model for Feminist Film Festivals, by Elizabeth Ellsworth. WOMEN'S INFORMATION ONLINE: The work of the National Council for Research on Women, by Mary Ellen S. Capek. NEWS FROM UW-LA CROSSE: By Sandi Krajewski. NEWS FROM UW-OSHKOSH: By Ellie Amico. NEW REFERENCE WORKS IN WOMEN'S STUDIES: New sources on: women's geographic resources, Third World resources, dissertations about women, business ownership, antifeminism, women in science, contemporary sculptors, women writers of Spain, women in Southern literature, Aphra Behn and Joyce Carol Oates. PERIODICAL NOTES: New periodicals on Australian women's studies, rock music, Jewish women, and national women's news. Special issues on Canadian women's history, international women, pornography and the law, North American Indian women, politics and government, women in the labor force, Southern women, black women in history, and women and the judiciary. Ceased publications: Between Ourselves: Women of Color Newspaper; Menses: The Periodical; and the Comparable Worth Newsletter. ITEMS OF NOTE: A tape series on women in U.S. history; microfilm of a nineteenth century British women's periodical; FBI files on the women's movement; a directory of national women's organizations; a resource collection on sexual assault; a report on women and music; a research summary on the economics of work and home; a package program for mid-life women; two fact kits on women's issues; three catalogs of rare and out-of-print books on women; a United Nations catalog of films on women; a women's taping service in Canada; and more. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES: A directory of Canadian feminist periodicals and an annotated bibliography on mother/daughter relationships in young adult fiction. BOOK REVIEWS: Forgotten warriors: women and the Vietnam experience, by Douglas Bradley. Nurturing daughters in recent young adult fiction, by Jan Savage. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews